Trait Impulsivity and Choice Impulsivity in Young Adult Students With Probable Binge Eating Disorder - Yan, Wan-Sen; Zheng, Dan-Hui; Liu, Meng-Meng (Frontiers in Psychiatry, 2022)
Background: Binge Eating Disorder (BED) as a public health problem has been included in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). Akin to addictive disorders, impulsivity-related neuropsychological constructs might be potentially involved in the onset and development of BED. However, it remains unclear which facets of impulsivity are connected to overeating and binge eating behaviors among non-clinical populations. The present study aimed to detect the relationship between impulsivity and binge eating both on the personality-trait and behavioral-choice levels in undiagnosed young adults. Methods: Fifty-eight individuals with probable BED and 59 healthy controls, matched on age, gender, and educational level, were assessed by using a series of self-report measurements, including the Barratt Impulsiveness Scale (BIS-11), UPPS-P Impulsive Behaviors Scale (UPPS-P), Delay Discounting Test (DDT), and Probability Discounting Test (PDT). Results: Multivariate analysis of variance models revealed that compared with healthy controls, the probable BED group showed elevated scores on the BIS-11 Attentional and Motor impulsiveness, and on the UPPS-P Negative Urgency, Positive Urgency, and Lack of Perseverance. However, the probable BED subjects had similar discounting rates on the DDT and PDT with healthy controls. Regression models found that Negative Urgency was the only positive predictor of binge eating behavior. Conclusions: These findings suggested that typical facets of trait impulsivity, which have been recognized in addictive disorders, were associated with binge eating in young adults, whereas choice impulsivity was not aberrantly seen in the same probable BED sample. This study might promote a better understanding of the pathogenesis of BED.